2013
DOI: 10.3389/fphar.2013.00109
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal serotonin depletion unmasks differences in the hyperlocomotor effects of phencyclidine and MK-801: quantitative versus qualitative analyses

Abstract: Antagonism of N-methyl-D-aspartate (NMDA) receptors by phencyclidine (PCP) is thought to underlie its ability to induce a schizophrenia-like syndrome in humans, yet evidence indicates it has a broader pharmacological profile. Our previous lesion studies highlighted a role for serotonergic projections from the median, but not dorsal, raphe nucleus in mediating the hyperlocomotor effects of PCP, without changing the action of the more selective NMDA receptor antagonist, MK-801. Here we compared locomotor respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Locomotor hyperactivity is a prominent component of the behavioral syndrome induced by competitive and uncompetitive NMDAR antagonists with psychotomimetic effects (Sturgeon et al, 1979; Mattia et al, 1986; Lehmann-Masten and Geyer, 1991; Danysz et al, 1994; Bakshi et al, 1999; Imre et al, 2006; Adams et al, 2013). Importantly, although many stimulant drugs increase locomotor activity, multivariate assessments in the BPM have shown that the effects of PCP and MK-801 on unconditioned motor activity are qualitatively distinct from those produced by other stimulant classes (Lehmann-Masten and Geyer, 1991; Krebs-Thomson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Locomotor hyperactivity is a prominent component of the behavioral syndrome induced by competitive and uncompetitive NMDAR antagonists with psychotomimetic effects (Sturgeon et al, 1979; Mattia et al, 1986; Lehmann-Masten and Geyer, 1991; Danysz et al, 1994; Bakshi et al, 1999; Imre et al, 2006; Adams et al, 2013). Importantly, although many stimulant drugs increase locomotor activity, multivariate assessments in the BPM have shown that the effects of PCP and MK-801 on unconditioned motor activity are qualitatively distinct from those produced by other stimulant classes (Lehmann-Masten and Geyer, 1991; Krebs-Thomson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, those investigators also reported that MXE does not alter locomotor activity when administered to Sprague-Dawley rats at doses up to 5 mg/kg. The lack of an effect of MXE is surprising because locomotor hyperactivity is a prominent component of the behavioral syndrome induced by NMDAR antagonists in rodents (Sturgeon et al, 1979; Mattia et al, 1986; Lehmann-Masten and Geyer, 1991; Danysz et al, 1994; Imre et al, 2006; Adams et al, 2013). The locomotor stimulation produced by NMDAR antagonists is often used as a preclinical measure of their psychotomimetic effects.…”
mentioning
confidence: 99%
“…After injection, the mice were allowed to explore the arena for a further 2 hours, with distance travelled data automatically calculated in 5-minute bins. Raw 50-msec-resolution data files were used for analysis of patterns of exploration ( Paulus and Geyer, 1991 ; Perry et al, 2009 ; Adams et al, 2013 ). Sequential patterns of exploration were defined by the measure entropy, which describes whether movements are repetitive (low entropy) or random (high entropy).…”
Section: Methodsmentioning
confidence: 99%
“…Using conventional manual scoring, we verified PCP -induced asociality whereby rats exhibited significant reductions in time spent allogrooming, pouncing and pinning compared to those treated with saline ( (Adams et al, 2013) and between 5 and 75 min (Sturgeon et al, 1979). Unlike conventional outof-cage locomotor assays, homecage analysis permitted a 24 h profile of PCP.…”
Section: Effect Of Pcp On Social Activitymentioning
confidence: 99%